Synchrotron X-ray study of electromigration, whisker growth, and residual strain evolution in a Sn Blech structure. (June 2022) - Lee, Pei-Tzu; Hsieh, Wan-Zhen; Lee, Cheng-Yu; Tseng, Shao-Chin; Tang, Mau-Tsu; Chiang, Ching-Yu; Kao, C.R.; Ho, Cheng-En
Abstract: Synchrotron X-ray analysis of the Sn electromigration behavior and Sn whisker growth in a Blech structure using nano-X-ray fluorescence microscopy and white beam Laue nanodiffraction was conducted. Sn depletion at the cathode and whisker/extrusion formation at the anode were characterized in-situ, and the results obeyed the electromigration kinetics. This electromigration scenario gradually decayed because of the counterbalance between electron wind force and back stress. White beam Laue nanodiffraction analysis showed that a noticeable compressive deviatoric stress in the direction of electron flow built up at the anode of Sn strips, particularly in the roots of Sn whiskers, confirming that electromigration-induced atomic accumulation occurred downstream in a strip and that Sn whiskering was closely related to internal stress resulting from atomic accumulation in confined segments. Finally, a theoretical model based on fundamental electromigration theory revealed that Sn diffused predominately through lattice and grain boundary paths at Sn homologous temperature of 0.6. Graphical abstract: Image, graphical abstract